2008
DOI: 10.3155/1047-3289.58.8.1077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Driving Conditions on Diesel Exhaust Particulates

Abstract: Four driving conditions were examined to characterize how speeds and loads of a medium-duty diesel engine affect resultant diesel exhaust particulates (DEPs) in terms of number concentrations (Յ400 nm), size distribution, persistent free radicals, elemental carbon (EC), and organic carbon (OC). At the medium engine load (60%), DEPs surged in number concentrations at around 40 -70 nm, whereas DEPs from the full engine load (100%) showed a distinctive bimodal distribution with a large population of 30 -50 nm and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…This is a lower limit given that radical decay is occurring at the same time as radical formation. To place this in context, we note that this value of radical content is comparable to values reported by Gehling and Dellinger who measured EPFR concentrations in ambient particulate matter, and found between 2.02 Â 10 16 -3.48 Â 10 18 radicals per g. 7 EPFR concentrations on diesel exhaust particles have also been previously reported to be in this range by Lim et al who found 1.23 Â 10 18 radicals per g. 32 Radical concentrations on the order of 10 18 have also been reported for n-hexane soot particles. 33 It is possible that each study is measuring roughly the same levels of radicals because they undergo self-reaction at higher levels, thus limiting the maximum concentration.…”
Section: Pccp Papersupporting
confidence: 87%
“…This is a lower limit given that radical decay is occurring at the same time as radical formation. To place this in context, we note that this value of radical content is comparable to values reported by Gehling and Dellinger who measured EPFR concentrations in ambient particulate matter, and found between 2.02 Â 10 16 -3.48 Â 10 18 radicals per g. 7 EPFR concentrations on diesel exhaust particles have also been previously reported to be in this range by Lim et al who found 1.23 Â 10 18 radicals per g. 32 Radical concentrations on the order of 10 18 have also been reported for n-hexane soot particles. 33 It is possible that each study is measuring roughly the same levels of radicals because they undergo self-reaction at higher levels, thus limiting the maximum concentration.…”
Section: Pccp Papersupporting
confidence: 87%
“…The different thermal characteristics of the two EC groups are consistent with combustion conditions that are known to generate the respective particle sizes with which the two EC groups are associated. That is, production of nuclei-mode particles is favored under conditions of low engine loads while production of larger particles (100-400 nm) is favored under conditions of high engine loads (Lim et al 2008).…”
Section: Resolving Ec and Oc Using Positive Matrixmentioning
confidence: 99%
“…20 The results suggested that as the load is increased with the increase of the throttle valve opening to offer enough fuel to maintain power, the total number concentration is raised. 21,22 The total number concentration is decreased with the increase of ethanol because the oxygen content of fuel is raised and better combustion is produced. 6 Figures 3-5 show the effect of various fuels on CO, HC, and NO x emissions, respectively.…”
Section: Results and Discussion Characterization Of Pm Emissionsmentioning
confidence: 99%